Healthy people, healthy land: driving sustainable food systems transformation with community agroecological values and Indigenous food systems planning in Kakisa, Northwest Territories, Canada - Temmer, Jennifer; Spring, Andrew; Chicot, Lloyd; Simba, Ruby (Frontiers in Agronomy, 2025)
Food systems in northern Canada are under severe pressure brought on by climate change, colonial policies, resource extraction, settler migration, dispossession from ancestral lands, and changing ways of life. As communities seek to nurture more resilient food systems, agroecology is emerging as a relevant food system framing to address these challenges as it balances new forms of sustainable food production with traditional food practices and connects them to on-going struggles for self-sufficiency and Indigenous food sovereignty. This article showcases insights from a community-driven, food systems planning project in Northwest Territories, Canada that incorporates agroecology rooted in Indigenous values, principles, and Traditional Knowledge of the region. Using participatory action research, the Ka’a’gee Tu First Nation (KTFN) designed a vision for their food system structured by the Community Agroecological Values Framework (CAVF). The CAVF, co-created with KTFN, builds on the community capitals framework and northern agroecology dialogues to foster a holistic approach to Indigenous food systems planning. Through a workshop, participatory mapping, and storytelling, community members reflected on existing food projects and provided input on future developments. KTFN used this process to connect their food system with multiple components of agroecology in the North, including land stewardship, sustainable livelihoods, cultural resurgence, social cohesion, good governance, and human capacity, aligning them with Dene values of holistic well-being for people and the environment. This article shares a case study of how KTFN is combining participatory, values- and place-based planning with agroecology to strengthen their food system, advance self-sufficiency, and promote food sovereignty in the face of climate uncertainties.